1992
DOI: 10.1037/1040-3590.4.1.77
|View full text |Cite
|
Sign up to set email alerts
|

Cross-validation of a psychological test battery to detect faked insanity.

Abstract: Attempts were made in these 2 studies of simulated insanity to enhance ecological validity: Experimental fakers were given potent monetary incentives to conceal their deception; psychiatric inpatients and convicted felons were used in criterion groups; and subjects took a battery of psychological tests that varied in task demands. In Experiment 1,8 predictor variables drawn from the MMPI, Bender Gestalt, and a newly developed Malingering Scale were used to derive a single discriminant function that best differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 29 publications
2
21
0
1
Order By: Relevance
“…Untersuchungen zur Brauchbarkeit der F-Skala,Simulation zu erkennen,haben unterschiedliche Ergebnisse erbracht [6]. Dementsprechend haben Wissenschaftler verschiedene CutoffWerte für die F-Skala bei einzelnen Untersuchungspopulationen diskutiert [2,3,21].…”
Section: "Strukturierter Fragebogen Simulierter Symptome"unclassified
“…Untersuchungen zur Brauchbarkeit der F-Skala,Simulation zu erkennen,haben unterschiedliche Ergebnisse erbracht [6]. Dementsprechend haben Wissenschaftler verschiedene CutoffWerte für die F-Skala bei einzelnen Untersuchungspopulationen diskutiert [2,3,21].…”
Section: "Strukturierter Fragebogen Simulierter Symptome"unclassified
“…Finally, participants completed a Dutch translation of the vocabulary and abstraction subtests of the Malingering Scale (MS) developed by Schretlen et al (1992). The 26 items of the vocabulary subtest present target words and for each target, the participant has to choose from two alternative words the one that has a similar meaning as the target word.…”
Section: Methodsmentioning
confidence: 99%
“…Sample items from the Dutch version of the vocabulary and abstraction subtests of the Malingering Scale (Schretlen et al, 1992 …”
Section: Appendixmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the F and Fb scales provided the best overall discrimination between authentic and simulated profiles, although both the Fake-Bad scale and the F-K index proved better suited for more refined discriminations. While some researchers (Rogers, 1988;Schretlen, Van Gorp, Wilkins, & Bobholz, 1992) have suggested that "subjects in malingering studies should be offered incentives for successful fabrication" (Wetter et al, 1993, p. 317), it remains to be tested whether simulations are as successful if the punishment for detection is relatively severe. Future research might consider an assessment of both the contribution of (a) incentives to succeed and (b) punishment from failure to succeed at disorder simulation.…”
Section: Discussionmentioning
confidence: 99%